Tumoral cutaneous rhinosporidiosis: Case report and review of literature - Nayantrishna Nath; Santanu Subba; Sanjay K. Giri; Priyanka Pant; Aparna Kanungo; Anurag Mishra; Pritinanda Mishra (Indian Journal of Pathology and Microbiology)
Rhinosporidiosis is a chronic granulomatous disease caused by Rhinosporidium seeberi commonly affecting nasal mucosa, conjunctiva, and urethra. Subcutaneous tumor nodule presentation is rare and often mimics as sarcoma. Such tumoral rhinosporidiosis has been reported rarely. This report describes a 60-year male who presented with a solitary, firm, nontender swelling in posterior aspect of right leg with an ulcer and mimicking clinically as soft tissue sarcoma. Histopathology was diagnostic. Surgical excision was found to be useful.